Application of Frequency Diversity to Suppress Grating Lobes in Coherent MIMO Radar with Separated Subapertures. (8th June 2009) - Zhuang, Long; Liu, Xingzhao
Abstract : A method based on frequency diversity to suppress grating lobes in coherent MIMO radar with separated subapertures is proposed. By transmitting orthogonal waveforms fromM separated subapertures or subarrays, M receiving beams can be formed at the receiving end with the same mainlobe direction. However, grating lobes would change to different positions if the frequencies of the radiated waveforms are incremented by a frequency offsetΔ f from subarray to subarray. Coherently combining theM beams can suppress or average grating lobes to a low level. We show that the resultant transmit-receive beampattern is composed of the range-dependent transmitting beam and the combined receiving beam. It is demonstrated that the range-dependent transmitting beam can also be frequency offset-dependent. Precisely directing the transmitting beam to a target with a known range and a known angle can be achieved by properly selecting a set ofΔ f . The suppression effects of different schemes of selectingΔ f are evaluated and studied by simulation.